2020
DOI: 10.15381/rpb.v27i2.17876
|View full text |Cite
|
Sign up to set email alerts
|

Physiognomic responses of páramo tussock grass to time since fire in northern Ecuador

Abstract: Ecologically-sound management plans for high-altitude grasslands of the Andes depend on an understanding the responses of plants to fire, especially the dominant tussock grasses. This study considers physiognomic responses of tussock grass in 13 sites in northern Ecuador with a known fire history, with time since fire 0.5–10 y, and a control site which had not been burned for at least 40 y. At each site, we assessed vegetation height, basal cover of the tussocks, and the ratio of dead:live leaves in tussocks. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…In this second phase, tussock grasses increase their dominance. Gutiérrez‐Salazar and Ramsay (2020) have shown that the height of the tussocks increases steadily during this phase, resulting in a consistent shading effect and decline in temperature at ground level. The dominance‐controlled plant community during phase 2 is thus characterised by the suppression of potential competitors by the tussocks.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…In this second phase, tussock grasses increase their dominance. Gutiérrez‐Salazar and Ramsay (2020) have shown that the height of the tussocks increases steadily during this phase, resulting in a consistent shading effect and decline in temperature at ground level. The dominance‐controlled plant community during phase 2 is thus characterised by the suppression of potential competitors by the tussocks.…”
Section: Discussionmentioning
confidence: 91%
“…Tussock plants are rarely killed by fires (Hofstede et al, 1995) as their deeply‐seated shoot apices and buds are protected against heat in the centre of the tussock base (Laegaard, 1992; Ramsay & Oxley, 1996). Nevertheless, partial mortality is often observed, leading to fragmentation of plants and a smaller basal area (Laegaard, 1992; Ramsay, 1999; Suárez & Medina, 2001; Gutiérrez‐Salazar & Ramsay, 2020). In the initial recovery phase after a fire, there is a tussock‐building phase caused by the growth of surviving fragments and recruitment of new seedlings in open areas (Ramsay & Oxley, 1996; Vargas‐Ríos, 1997; Ramsay, 2001; Vargas Ríos, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations